Applications in Ilal Al-Hadith by Ibn Abi Hatim Al-Razi: The Ninety-Seventh Issue as an Example - Maria Bassam Mohammed Abdelrahman (دراسات: علوم الشريعة والقانون, 2022)
Objectives: This study aims to reveal the importance of critical practice, and to explain the methodology of reasoning in the ninety-seventh issue in Kitaab Al’ilal by Ibn Abi Hatim Al-Razi with the identification of the cause and the jurisprudential subject. It also aims to compare between the explanatory plan adopted by Ibn Abi Hatim and other critics who dealt with the same issue.